Calculation of Effective Indicators of Relief Section Height - L.A.Ilmurodova; A.M.Axunjanov; L.T.Ibragimov (Research Parks Publishers, 2022)
This article discusses differential dimensions of the height of the relief section are established using the primary informative and geoindicator characteristics of the distribution of the ends of the local relief heights, and on the basis of these, the morphometric properties of the distinguishing features of the relief surface are taken into account.